CHROMOGRANIN-A IN THE DIAGNOSIS OF PROSTATE CANCER - A. V. Sivkov; N. G. Keshishev; G. D. Efremov; G. A. Kovchenko; A. A. Trudov; L. M. Nikonova; F. D. Romikh (Исследования и практика в медицине, 2015)
The principal marker of neuroendocrine differentiation (NED) is chromogranin A (HGA). The purpose of this work is to determine the role of NED in diseases of the prostate gland by the level of HGA.Materials and methods. The study included 304 men with various diseases of the prostate: BPH - 20; chronic prostatitis (CP) - 22; BPH and prostatic low-grade intraepithelial neoplasia (BPH+LDPIN) - 50; BPH and high degree PIN (BPH+HGPIN) - 32; localized prostate cancer (LPC) - 80; locally advanced PCA (LAPC) - 21; CRPC - 51. The last group United in patients LPC, LAPC and metastatic prostate cancer. All these groups of patients were performed blood sampling fasting with further definition of the level of HGA in serum by enzyme immunoassay. The reference values of HGA for this method are ranged from 0 to 3 nmol/L.Results. During the analyzing of the results of the study they revealed a general trend of increasing of mean values of HGA of serum with the growth stage of prostate cancer, with a maximum of patients with CRPC. According to the analysis they revealed no significant correlation between age and HGA (r = 0,05) among all study groups. They noted the persistent correlation (r = 0,32; p <0,001) between HGA and PSA levels among all studied groups of patients. They traced some relationship between the amount of points Gleason and HGA (r = 0,19; p <0,05) in cases of LPC, LAPC and CRPC. Defining the relationship between HGA and stage of prostate cancer (LPC, LAPC and CRPC), we also found a correlation (r = 0,31, p <0,005) among these groups of patients.Conclusions. HGA is a high interest for the early detection CRPC. Also with the help of HGA it seem to be quite promising to discover the most aggressive forms of prostate cancer. Definition of NED-tumor may be necessary for the analysis of a comprehensive approach to prostate cancer treatment selection.